Ringol: An Alternative Sport for Physical Education Classes. Systematic Literature Review - González-Coto, Víctor A. (2024)
Introduction: Alternative Games and Sports arise with the intention of introducing new alternatives that make possible a more logical evolution of the game and sport, favouring motivation, participation, and enjoyment to escape from the monotony of traditional methodologies. Objetive: Therefore, the aim of this paper is to carry out a systematic review of the literature on the game and alternative sport Ringol. Methodology: For this, a document search has been carried out in the following databases: Google Scholar, Web of Science, Scopus and Sportdiscus. For the search of the documents, the following keywords have been used: "Ringol", "Physical education", and "Primary education", obtaining a final number of 6 valid documents, identified until November 2022. To limit the search and obtain the most appropriate documents, a series of inclusion and exclusion were established. Results: The results show that most of the documents are Academic Projects, written in Spanish and found in Google Scholar, with a predominance of Sports Information. Conclusions: The documents analyzed show that the main benefits of Ringol are egalitarian practice, the development of motor skills and actions such as participation, motivation, cooperation, and respect. The educational level where these projects are carried out is both Primary Education and Secondary Education. Finally, this review serves as a basis and guide for future research on the Ringol.